RAM cannula with Cannulaide versus Hudson prongs for delivery of nasal continuous positive airway pressure in preterm infants: an RCT - Shravani Maram; Srinivas Murki; Sidharth Nayyar; Sandeep Kadam; Tejo Pratap Oleti; Rajendra Prasad Anne; Saikiran Deshobhotla; Deepak Sharma; Subhash Arun; Praveen Rao Vadije (Scientific Reports, 2021)
Abstract Nasal continuous positive airway pressure (nCPAP) is the standard non-invasive respiratory support for newborns with respiratory distress. Nasal injury is a common problem with the interfaces used. To compare the incidence and severity of nasal injury in neonates with respiratory distress and supported on nCPAP with Hudson prong or RAM cannula with Cannulaide, a semipermeable membrane. This is an open-label, parallel-arm, gestational age-stratified, bi-centric, randomized control trial including neonates between 28 and 34 weeks gestational age and birth weight > 1000 g needing nCPAP. The size of the interface was chosen as per the manufacturer’s recommendation. Of the 229 neonates enrolled, 112 were randomized to RAM cannula with Cannulaide and 117 to Hudson prong. The baseline characteristics were similar. Any nasal injury at CPAP removal was significantly lower in the RAM cannula with Cannulaide group [6 (5.4%) vs. 31 (26.4%); risk ratio—0.77 (95% CI 0.69–0.87); p = 0.0001]. The incidence of moderate to severe nasal injury, need for mechanical ventilation within 72 h of age, duration of oxygen, and requirement of nCPAP for > 3 days were similar. For preterm infants on nCPAP, RAM cannula with Cannulaide, compared to Hudson prongs, decreases nasal injury without increasing the need for mechanical ventilation. Trail registration: CTRI/2019/03/018333, http://www.ctri.nic.in .